Review of solar and low energy cooling technologies for buildings - Florides, Georgios A.; Tassou, Savvas A.; Kalogirou, Soteris A.; Wrobel, L. C. (My University, 2002)
The objective of this paper is to examine solar cooling and low energy cooling technologies. A brief review of various cooling systems is presented, including solar sorption cooling, solar-mechanical systems, solar related air conditioning, and other low energy cooling technologies. The relative efficiencies and applications of the various technologies are presented. These technologies can be utilized to reduce both the energy consumption and environmental impact of mechanical cooling systems.
Keywords: Solar cooling systems; Passive systems